2022
DOI: 10.1111/php.13658
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptomic and Proteomic Analyses Reveal the Different Responses to UVA and UVB Radiation in Human Keratinocytes

Abstract: Ultraviolet (UV) radiation from sunlight is a major risk factor for many cutaneous pathologies including skin aging and cancers. Despite decades of research, the different responses to UVA and UVB in human keratinocytes have not been systemically investigated. Here, we performed multi-omics to characterize the common and different changes in gene transcription and protein expression after exposure to UVB and UVA, respectively. Keratinocyte cells, treated with or without UV, were analyzed by TMT-labeled MS/MS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Based on our previous research, the combination of transcriptomic and proteomic analyses in our work revealed common and differential genes or proteins in human primary keratinocytes exposed to UVA and UVB [21]. By combing protein-protein interactions (PPI) and molecular complex detection method (MCODE) analyses, hub genes or proteins were discovered in each group, which could be the basis for subsequent research on the mechanism of skin damage caused by UV radiation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on our previous research, the combination of transcriptomic and proteomic analyses in our work revealed common and differential genes or proteins in human primary keratinocytes exposed to UVA and UVB [21]. By combing protein-protein interactions (PPI) and molecular complex detection method (MCODE) analyses, hub genes or proteins were discovered in each group, which could be the basis for subsequent research on the mechanism of skin damage caused by UV radiation.…”
Section: Discussionmentioning
confidence: 94%
“…In laboratory studies, the doses of UVA and UVB radiation given to cultured cells are typically higher than the ambient levels of these types of radiation that would be encountered during normal sun exposure. We chose 10 J/cm 2 of UVA or 30 mJ/cm 2 UVB as irradiation dose based on the previous study [21], which have shown that 10 J/cm 2 of UVA or 30 mJ/cm 2 UVB can cause cell damage and decrease cell survival rates without causing excessive harm and affecting cell growth status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation